This graph is like a hyperbole y = 1/x, but not exactly.

First, move it right for vertical asymptote be x = 4: y = c/(x-4).

Second, move it up for horisontal asymptote be y = 3: y = c/(x-4) + 3.

And to satisfy y(6) = 4 pick suitable c:c/(6-4) + 3 = 4, then c = 2.

So, y = 3 + 2/(x-4) is very similar to the graph.

Secure Information

Content will be erased after question is completed.

Enter the email address associated with your account, and we will email you a link to reset your password.

Forgot your password?

Sign Up